2019
DOI: 10.1007/s10100-019-00639-8
|View full text |Cite
|
Sign up to set email alerts
|

Occupational risk assessment with grey system theory

Abstract: The article proposes a new method of occupational risk assessment which uses the grey decision model. The method is called the grey occupational risk assessment model (GORAM). The presented method allows for combining measurable and qualitative factors in the process of occupational risk assessment through the use of expert knowledge. This method can be applied to the multifaceted occupational risk assessment of complex and uncertain sociotechnical systems. First, the article presents problems with currently u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…It is often the deadline of the construction period. During the construction process, it is necessary to ensure the normal work, study, and life of school teachers and students, so that the control of the construction period and environmental safety and hygiene are placed in a more important position [27]. e weight of subcontracting coordination is about 17%, only second after checking the construction period.…”
Section: Contract Management Sectionmentioning
confidence: 99%
“…It is often the deadline of the construction period. During the construction process, it is necessary to ensure the normal work, study, and life of school teachers and students, so that the control of the construction period and environmental safety and hygiene are placed in a more important position [27]. e weight of subcontracting coordination is about 17%, only second after checking the construction period.…”
Section: Contract Management Sectionmentioning
confidence: 99%
“…Methods included in the GST are widely used in practice, especially when information uncertainty manifests in the form of a small set of data (which renders it impossible to use statistical methods-e.g., with respect to short time periods), incomplete information or information burdened with inaccuracy or subjectivity [29]. The described application area of methods included in Grey System Theory spurred their growing popularity [30]. In recent years, using a number of grey models, the uncertainty within grey systems with economic, social, technical or even natural character has been modeled [31,32].…”
Section: Methodsmentioning
confidence: 99%
“…Among grey system models there are, e.g., grey prediction models, grey decision-making models, grey control models, and grey relations models [37]. The selected methods of information uncertainty modeling are included in Grey System Theory, when one of the three constructs is used in them-grey numbers, whitenization function, or distributed grey [30].…”
Section: Methodsmentioning
confidence: 99%
“…Oz et al 33 suggested an integrated risk assessment model based on Pythagorean fuzzy sets and the technique for order preference by similarity to ideal solution (TOPSIS) for examining the occupational hazards of a natural gas pipeline project. Based on grey system theory, Nowak et al 34 proposed a grey occupational risk assessment model for evaluating the risks of mechanics who are working in a manufacturing enterprise. Liu et al 2 introduced a hybrid OHS risk assessment model by integrating picture fuzzy sets and alternative queuing method to analyze the risk of occupational hazards in construction sites.…”
Section: Literature Reviewmentioning
confidence: 99%